The Evolving Partnership Between General Practitioners and Nurses: A Systematic Review of Roles, Coordination, and Clinical Effectiveness (The Review of Diabetic Studies, 2025)
General practitioners (GPs) and nurses constitute the core of primary healthcare delivery, yet the dynamics of their collaboration continue to evolve in response to rising healthcare demands, workforce shortages, and the shift toward patient-centered models. This systematic review examines the roles, coordination mechanisms, and clinical effectiveness associated with GP–nurse partnerships in diverse primary care settings. A structured search of literature published between 2016 and 2025 was conducted across PubMed, Scopus, Web of Science, and CINAHL. Studies were screened based on predefined inclusion criteria emphasizing interprofessional collaboration, shared care models, clinical outcomes, and organizational effectiveness. Evidence reveals that effective GP–nurse collaboration improves chronic disease management, enhances patient satisfaction, reduces hospitalization rates, and strengthens continuity of care. Furthermore, task-shifting and nurse-led clinical pathways significantly alleviate GP workload while preserving clinical quality. Key enablers of collaboration include defined scopes of practice, shared electronic health records, structured communication methods, and supportive leadership. However, role ambiguity, inconsistent training, and hierarchical barriers remain persistent challenges. This review highlights the importance of integrated care pathways, regulatory support, and advanced nursing competencies to optimize team-based primary healthcare.